PENGANGGARAN MODAL DALAM PENGAMBILAN KEPUTUSAN INVESTASI JANGKA PANJANG - Zattira, Reza; Jaka, Dhimas; Purnomo, Endri (Relasi : Jurnal Ekonomi, 2016)
Significant lack of planning in making an investment by a company. This is because in planning an investment project certainly require substantial funds, so that if it is not budgeted and calculated properly, it can result in the failure of investment projects that could cause a company suffered a great loss. This study discusses the capital budgeting of a project in the CV. X will buy a corn seed drying machine. In this study is discussed in detail how to calculate the initial investments, estimating revenue to be obtained by the company when the project is, how long the capital issued by the company to the investment project will be returned, and the most important thing is feasible or not it is an investment project planning. The method used in the calculation of capital budgeting is the payback period, discounted payback period, Net Present Value (NPV), and Internal rate of Return (IRR). In this study showed that planning the purchase of corn drying machine by CV X is received by calculating the payback period for 3 years 2 months 5 days, discounted payback period 3 years 10 months 21 days, NPV > 0 or NPV positive and IRR > cost of capital, there is 21,70% > 10,80%.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />